(untitled) (Research, Society and Development, 2022)
External assessments seek standardized assessment matrices in order to generate indicators of educational quality. Therefore, their knowledge and debate become fundamental in initial teacher training courses. Given this context, the objective of this research is to investigate the presence of contents and/or curricular components related to large-scale assessments in the syllabus of the Pedagogical Course Projects (PPC) of Degree in Biological Sciences of different HEIs, as well as to analyze the workload and bibliographies related to the theme. This documentary research presents a qualitative approach. Based on inclusion and exclusion criteria, the selection of PPCs was carried out, and data analysis was performed through the analysis of the content of the. It was possible to perceive that there is no presence of contents and/or curricular components that specifically address external and large-scale assessments. However, there are curricular components that, based on their objectives and menus, allow us to infer that there are possibilities for a dialogue about these assessments. Therefore, as it generates implications for the structuring of education, it would be important to reorganize the curriculum within the Biological Sciences Licentiate courses, considering that external assessments, in large part, directly imply the future locus of work.